Evaluation of Cardiac Involvement by Echocardiography in Children with Acute Meningococcemia - Semra Atalay; Hulya Kahraman; Saimin Karademir; Musa Kazim Caglar (Indonesian Pediatric Society Publishing House, 2018)
Myocarditis in acute meningococcemia is rare in children. Impaired cardiac contractile function may contribute to cardiovascular collapse in endotoxemia. We evaluated prospectively the clinical and echocardiographic findings in 25 consecutive children with acute meningococcemia. All of the patients had good prognostic indicators. Eleven (44%) of the 25 children bad echocardiographic evidence of myocardial dysfunction. The mean LVFS in these eleven children was 0.23 ± 6.00, as compared with the mean LVFS of0.34±8.87 in the remaining children. LVFS returned to normal within 7 days in all patients. We observed minimal pericardia/effusion in 4 patients (16%) that resolved within 3 days. We demonstrated that acute meningococcemia is frequently associated with myocardial dysfunction. We could not though, find the relation between myocardial dysfunction and mortality.